Conversion of a muco-supported complete prosthesis into fixed implant-supported prosthesis using the NeoConvert™ solution in a maxillary rehabilitation with guided surgery and immediate loading - Olaya, Carolina; Arenaza, Lina; Luna, Félix; Miyasawa, Erton; Freitas, Rubens; Fontão, Flávia (Brazilian Journal of Implantology and Health Sciences, 2024)
Modern dentistry has seen the development of different techniques aimed at improving patient satisfaction. Immediate loading and delivering a fixed implant-supported prosthesis at surgery time has become an option. This case report describes the clinical results of the immediate loading of a conventional complete denture converted into a fixed prosthesis on six implants placed under a guided surgery protocol. A male patient, systemically healthy, with total upper edentulism, attended the ILAPEO College to begin treatment with implants in the upper jaw. Six implants were placed under a guided surgery protocol, and then immediate loading was performed by converting the patient’s complete denture into a fixed prosthesis using the NeoConvert™ system. Immediate loading using the NeoConvert™ technique is a functional and predictable alternative, reducing clinical time and achieving great patient and clinician satisfaction.